Avaliação de diferentes adjuvantes agrícolas: análise das características físicos-químicas e efeito de dessecante aplicado na cultura de soja - Costa, Regina Neves Ubial (2024)
The constant search for sustainable and effective solutions in agriculture has led to the development of new products and technologies to improve the performance of agrochemicals. The objective of this study is to analyze, by comparison, the physicochemical characteristics of agricultural adjuvants, with the addition of soybean oil, associated with a herbicide/desiccant. The tests will be carried out in the physical infrastructure, at the State University – Unioeste – Toledo Campus, in the Instrumental Chemical Analysis Laboratory, and also at the State University – Unioeste – Cascavel Campus, in the Sustainable Technologies Laboratory – LABTES. To carry out the tests, the mixtures will be prepared, with the addition of the same herbicide, following the instructions of each manufacturer. Four repetitions will be carried out for each physical-chemical test: Critical Micellar Concentration Analysis (CMC); Ideal pH of the Adjuvant; Ideal Electrical Conductivity of the Adjuvant; Tendency to Foam Formation; Stability and Effect of Formed Layers; Decantation and Precipitation of the Adjuvant; Drop contact angle; turbidity. The collected data will receive both descriptive and experimental statistical treatment. These tests will be carried out on plant foliage to be defined and carried out in the laboratory, and will not be evaluated on plants outside a controlled environment.